2003
DOI: 10.1073/pnas.0330745100
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid deposition in the hippocampus and entorhinal cortex: Quantitative analysis of a transgenic mouse model

Abstract: Various transgenic mouse models of Alzheimer's disease (AD) have been developed that overexpress mutant forms of amyloid precursor protein in an effort to elucidate more fully the potential role of ␤-amyloid (A␤) in the etiopathogenesis of the disease. The present study represents the first complete 3D reconstruction of A␤ in the hippocampus and entorhinal cortex of PDAPP transgenic mice. A␤ deposits were detected by immunostaining and thioflavin fluorescence, and quantified by using high-throughput digital im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
108
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(116 citation statements)
references
References 53 publications
7
108
1
Order By: Relevance
“…The molecular layer of the dentate gyrus is one of the first regions to show amyloid deposition and synapse loss in the Tg2576 mouse model of AD (Su and Ni, 1998;Reilly et al, 2003;Dong et al, 2007). However, it is difficult to know the implications of increases in synapse density after memantine administration in Tg2576 mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular layer of the dentate gyrus is one of the first regions to show amyloid deposition and synapse loss in the Tg2576 mouse model of AD (Su and Ni, 1998;Reilly et al, 2003;Dong et al, 2007). However, it is difficult to know the implications of increases in synapse density after memantine administration in Tg2576 mice.…”
Section: Discussionmentioning
confidence: 99%
“…We focused our structural assessments on the hippocampal formation because these structures play a major role in learning and memory (Knowles, 1992;Bannerman et al, 2001) and is also a site for Ab deposition in AD patients (Probst et al, 1983;West et al, 2004) and in several transgenic mouse models of AD (Su and Ni, 1998;Reilly et al, 2003). Synapse loss induced by Ab remains a likely basis for the behavioral deficits observed in Tg2576 mice (Stern et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In transgenic mouse models of AD, β-amyloid deposits have been classified as diffuse or compact, with compact deposits being more frequently associated with neuritic changes (Reilly et al, 2003). Recent studies have shown that soluble, low-molecularweight (8-24 kDa) Aβ oligomers, referred to as β-amyloid-derived diffusible ligands, may be capable of producing neuronal dysfunction (Lambert et al, 1998;Walsh et al, 2002;Gong et al, 2003;Mattson, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Also, they are primary sites for β-amyloid deposition in APP transgenic mice (Su and Ni, 1998;Reilly et al, 2003). The perforant path that projects from the entorhinal cortex to the dentate gyrus is among the most vulnerable pathways in cortex with respect to both aging and AD pathology Gazzaley et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The value of biomarkers predicting conversion to clinical AD has limitations in the absence of tests sensitive to subtle cognitive changes in prodromal AD. Investigations using animal models of AD also indicate that the entorhinal cortex and perforant pathway input to the hippocampus are among the earliest affected and most vulnerable regions of Aβ pathology [29][30][31]. Spatial ability likely becomes affected in prodromal AD because Aβ selectively disrupts perforant pathway input to hippocampus from the entorhinal cortex.…”
Section: Introductionmentioning
confidence: 99%